The Influence Of Environment, Promotions And Price Perceptions On Clothing Purchase Decisions In Ptm Bengkulu City - Jessica Ghea Nofarera; Ratnawili (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
The title of this research is The Effect of Environment, Promotion and Price Perception on Clothing Purchasing Decisions at PTM Bengkulu City. This study aims to determine which factors are most dominant in influencing Purchasing Decisions. The research was conducted from November 2023 to January 2024. The sample of this research is consumers who have made purchases and have consumption experience at the Modern Traditional Market (PTM) Bengkulu City. This research uses quantitative methods on 170 respondents. The sampling technique is probability sampling, the method used in this research is quantitative method with Multiple Linear Regression analysis using SPSS 24 for windows. Based on the results of multiple linear regression, the regression equation Y = 1.189 + 0.438 (X_1) + 0.251 (X2) + 0.641 (X3) and the coefficient of determination Adjusted R Square (R2) obtained a value of 0.683 or around (68.3%). The research results and hypotheses in this study indicate that Environment, Promotion and Price Perception have a positive effect partially or simultaneously on consumer purchasing decisions at the Modern Traditional Market (PTM) Bengkulu City.